John Keep papers - Keep, John, 1781-1870.
Correspondence, speeches concerning slavery by Keep and Owen Lovejoy, autobiography, notes, record book, newspaper clippings, a Bible containing Keep family genealogical information, and brass plate portrait of Keep. Subjects include William Dawes, the purchase of the Cleveland American, and publication of a Liberty Party paper in Cleveland, Ohio. Correspondents include Levi Burnell, William Lloyd Garrison, and John Hiram Osborn.
In part, positive photocopy and typewritten transcripts.
Clergyman and abolitionist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Burnell, Levi, -- 1803-1881 -- Correspondence; Dawes, William, -- 1799-1881.; Garrison, William Lloyd, -- 1805-1879 -- Correspondence; Lovejoy, Owen, -- 1811-1864.; Osborn, John Hiram -- Correspondence; Keep family; Liberty Party (U.S. : 1840-1848); Cleveland American; American newspapers -- Ohio; Slavery; Abolitionists; Clergy